Elongation Patterns of Posterolateral Corner Reconstruction Techniques: Results Using 3-Dimensional Weightbearing Computed Tomography Simulation. Issue 4 (18th April 2022) - Hodel, Sandro; Hasler, Julian; Fürnstahl, Philipp; Fucentese, Sandro F.; Vlachopoulos, Lazaros
Background: The isometric characteristics of nonanatomic and anatomic posterolateral corner (PLC) reconstruction techniques under weightbearing conditions remain unclear. Purpose: To (1) simulate graft elongation patterns during knee flexion for 3 different PLC reconstruction techniques (Larson, Arciero, and LaPrade) and (2) compute the most isometric insertion points of the fibular collateral ligament (FCL) graft strands for each technique and report quantitative radiographic landmarks. Study Design: Descriptive laboratory study. Methods: The authors performed a 3-dimensional simulation of 10 healthy knees from 0° to 120° of flexion using weightbearing computed tomography (CT) scans. The simulation was used to calculate ligament length changes during knee flexion for the PLC reconstruction techniques of Larson (nonanatomic single-bundle fibular sling reconstruction), Arciero (anatomic reconstruction with additional popliteofibular ligament graft strand), and LaPrade (anatomic reconstruction with popliteofibular ligament graft strand and popliteus tendon graft strand). The most isometric femoral insertion points for the FCL graft strands were computed within a 10-mm radius around the lateral epicondyle (LE), using an automatic string generation algorithm (0 indicating perfect isometry). Radiographic landmarks for the most isometric points were reported. Results: Median graft lengthening during knee flexion was similar for the anterior graft strands of all 3 techniques. The posterior graft strands demonstrated significant differences, from lengthening for the Arciero (9.9 mm [range, 6.7 to 15.9 mm]) and LaPrade (10.2 mm [range, 4.1 to 19.7 mm]) techniques to shortening for the Larson technique (−17.1 mm [range, −9.3 to −22.3 mm]; P < .0010). The most isometric point for the FCL graft strands of all techniques was located at a median of 2.2 mm (range, −2.2 to 4.5 mm) posterior and 0.3 mm (range, −1.8 to 3.7 mm) distal to the LE. Conclusion: Overconstraint can be avoided by tensioning the posterior graft strands in the Larson technique in extension, and in the Arciero and LaPrade techniques at a minimum of 60° of knee flexion. The most isometric point was located posterodistal to the LE. Clinical Relevance: The described isometric behavior of nonanatomic and anatomic PLC reconstruction techniques can guide optimal surgical reconstruction and prevent graft lengthening and overconstraint of the lateral compartment in knee flexion. Repetitive graft lengthening has been found to be associated with graft failure, and overconstraint favors lateral compartment pressure and cartilage degeneration.